Atomic Layer Deposition of i-Sb2S3/p-NiO Thin Layers into Anodic Alumina Membranes for Photoelectrochemical Water Splitting - Barr, M. K.S.; Assaud, Loic; Wu, Yanlin; Bachmann, Julien; Santinacci, L. (ECS Transactions, 2015)
A nanostructured photoelectrode was fabricated by atomic layer deposition (ALD) of NiO and Sb2S3 in nanoporous alumina. The fabrication, i.e. the successive ALD of NiO and Sb2S3, and the characterization of the arrays of coaxial NiO/Sb2S3 junction by electron microscopies are first reported. The optical and photoelectrochemical preliminary testing of the combination of such extremely thin absorber, Sb2S3, with a p-type semiconductor, NiO, are proposed in a second part. Although the photoconversion performances should be improved, the present work demonstrates validity of the concept.
EAM Import::2019-03-13